Hydrothermal conditions of the temporal variability of the phytoproductive functioning: case study of the Burtinskaya steppe landscape (Southern Urals) - Khoroshev, A.V.; Kalmykova, O.G.; Ashikhmin, A.P. (Fundamental and Experimental Biology, 2022)
The interpretation of a geographic landscape as a geosystem requires evidence that, under certain conditions, an external signal has a similar response in its spatial elements. The article examines the similarities and dif-ferences in the response of units in the steppe landscape of the Southern Urals (Burtinskaya steppe) to varying hydrothermal conditions. The Normalized Difference Vegetation Index (NDVI) is used as an indicator of intra-seasonal variability in phytoproduction performance. 110 standardized increments of NDVI during the growing seasons in 2010–2020 were ranked and interpreted as types of dynamics in comparison with back-ground modal values. The occurrence and diversity of types of phytomass dynamics within the model units (gullies, ridges, and interfluve flat surfaces) vary depending on hydrothermal conditions and the length of the time interval between measurements. The integrity of the unified response in the landscape is enhanced during dry periods, when changes in phytomass in gullies and on ridges differ little from those on spatially dominant slopes and flat surfaces. Strong deviations from the background dynamics often appear at intervals of up to 2 months, but are compensated for within 4–5 months. The dynamics of hydrothermal conditions over the entire growing season manifests itself in phytomass changes in a similar way over the landscape, which proves the connection between the spatial and temporal parameters of landscape organization. Depending on the landform, phytocenoses adapt to the late summer moisture deficit either by transitioning to another stable state of structure while maintaining the intensity of functioning (self-organization), or by maintaining the structure while reducing the intensity of functioning (self-regulation).